Understanding the civic role of community colleges: assessing factors that influence leadership decision-making - Villanueva-Saucedo, Deanna (My University, 2026)
This study examines how community college leaders conceptualize and make decisions about their institution’s civic role. Grounded in the sector’s historic commitment to civic engagement, the study responds to concerns about declining civic literacy and increasing polarization. Using quantitative-leading mixed methods research with an explanatory sequential design, survey data from community college leaders in the Desert Southwest United States informed follow-up qualitative interviews. Findings indicate that decision-making is shaped by a combination of institutional constraints, environmental pressures, and personal factors. Leaders balance competing priorities such as limited resources and public scrutiny, while also relying on personal values and experiences. Results further reveal variation in how leaders define and operationalize civic engagement, ranging from passive community access to more active, partnership-driven approaches. This study contributes to the literature by identifying key influences on leadership decision-making and highlighting the lack of a consistent framework for civic engagement in community colleges. Implications point to the need for clearer definitions, targeted leadership development, and stronger alignment between civic outcomes and institutional priorities.
Keywords: Community college; Civic engagement; Leadership; Decision-making